A Novel Human Antibody, HF, against HER2/erb-B2 Obtained by a Computer-Aided Antibody Design Method. (November 2021) - Qiao, Chunxia; Lv, Ming; Li, Xinying; Lang, Xiaoling; Lv, Shouqin; Long, Mian; Li, Yan; Geng, Shusheng; Lin, Zhou; Shen, Beifen; Feng, Jiannan
Abstract: Fully human antibodies have minimal immunogenicity and safety profiles. At present, most potential antibody drugs in clinical trials are humanized or fully human. Human antibodies are mostly generated using the phage display method ( in vitro ) or by transgenic mice ( in vivo ); other methods include B lymphocyte immortalization, human–human hybridoma, and single-cell polymerase chain reaction. Here, we describe a structure-based computer-aided de novo design technology for human antibody generation. Based on the complex structure of human epidermal growth factor receptor 2 (HER2)/Herceptin, we first designed six short peptides targeting the potential epitope of HER2 recognized by Herceptin. Next, these peptides were set as complementarity determining regions in a suitable immunoglobulin frame, giving birth to a novel anti-HER2 antibody named "HF, " which possessed higher affinity and more effective anti-tumor activity than Herceptin. Our work offers a useful tool for the quick design and selection of novel human antibodies for basic mechanical research as well as for imaging and clinical applications in immune-related diseases, such as cancer and infectious diseases.